The Relationship of Community Social Control to The Boarding School Institution - Maisyanah Maisyanah; Redite Kurniawan (Al Hikmah: Journal of Education, 2023)
This study aims to analyze the social relationship between the community and pesantren educational institutions and examine the social control that occurs in them. The research method used is a literature study by collecting data through identification of data sources, data collection, data selection, and data analysis. Thematic analysis is used in this research which focuses on an in-depth understanding of certain themes or patterns in the data collected. The results of data analysis show that the social relationship between the community and pesantren is in the form of a reciprocal relationship, where both parties influence and interact with each other. Pesantren as educational institutions play an important role in providing quality formal and non-formal education for community children, as well as providing moral and religious education for the community. Nevertheless, this study also found several cases that need to be addressed in an effort to improve the quality of relationships and social control between the community and pesantren for better educational sustainability in the future. The results of data analysis show that there are cases of controversy that lead to the need for social relations between the community and pesantren as a form of reciprocal relationship.